Pengaruh Kinerja Keuangan terhadap Harga Saham pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Kanji, Lusiana; Mikhailah, Amera; Aurelia, Almira; Zuldjibran, Rachmad; Idris, Aryadi (Al-Buhuts, 2023)
This study aims to determine and analyze the effect of Current Ratio, Return On Equity, and Earning Per Share on Stock Prices in Property and Real Estate Companies listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from financial reports and stock data using a purposive sampling technique. The population is Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2019-2021 period with a total of 34 observations. While the samples taken amounted to 93 observations. The results of the research variable data have been tested on the classical assumptions in the form of normality assumptions, auticorrelation assumptions, and their heteroscedasticity assumptions. Methods of data analysis using multiple linear regression techniques.The results of this study indicate that the Current Ratio has no effect on stock prices, Return On Equity and Earning Per Share have a positive and significant effect on stock prices